Analisis Usaha Agroindustri Keripik Ubi - -, Nimat (Jurnal Ilmiah Mahasiswa Fakultas Pertanian, 2016)
Potato chips is a food production process is quite simple, potato chips is also a food that is highly favored by the people ranging from children, adults and the elderly. But in running the business entrepreneur potato chips have not done an evaluation of business being run and also do not perform financial analysis on business so unknown amount of revenues and profits in each production period on business. The research objective was to analyze the financial feasibility of agro-industry enterprises potato chips. Data collection methods used were direct interviews with respondents. Results of financial analysis shows that the value of Return Cost Ratio (RCR) of 1.50 which indicates that every single rupiah spent entrepreneur will make a profit of 1.50, BEP production price of Rp. 535 / pack, BEP production volume as much as 1,003 packs / production period. From the results it can be concluded that the agro-industry effort potato chips Mrs. Sunarti feasible.Keywords: business, financial results.